Epistemological foundations of economics: the philosophical problem of ranking - Szabó, Balázs; Nemeskéri, Zsolt (Acta Cultura et Paedagogicae, 2023)
In our article, we examine the philosophical challenges of ranking that are economically significant from multiple angles. With our findings, we want to demonstrate that ranking in the actual world is a far more sophisticated, partially context-dependent behaviour enacted via specialised decision-making systems. In some ranking scenarios, the exact preference relation may vary depending on whatever basic set of phenomena we are discussing. On this basis, we can limit the scope of economic modelling to exclude, for instance, aesthetic value judgments. In the study, we would like to demonstrate the importance of the philosophical substantiation of economic phenomena